2012
DOI: 10.1097/bpo.0b013e318269543b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Preoperative Antibiotics in Pediatric Orthopaedic Surgery

Abstract: Level III, retrospective comparative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…15 The overall rate of surgical-site infection in our study (1.8%) was consistent with that reported in the literature for patients undergoing CRPP of supracondylar humerus fractures. 7,[9][10][11][12] The majority of infections were superficial and effectively treated with antibiotics, which is also consistent with current literature. Our results demonstrated that postoperative antibiotic administration had no effect on the rate of surgical-site infection.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…15 The overall rate of surgical-site infection in our study (1.8%) was consistent with that reported in the literature for patients undergoing CRPP of supracondylar humerus fractures. 7,[9][10][11][12] The majority of infections were superficial and effectively treated with antibiotics, which is also consistent with current literature. Our results demonstrated that postoperative antibiotic administration had no effect on the rate of surgical-site infection.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, it has been shown that pediatric patients who do not receive preoperative antibiotics before this procedure and other minimally invasive orthopaedic procedures are not at higher risk of developing a surgical-site infection compared with patients who receive preoperative antibiotics. 8,9,11 Postoperative antibiotic use has not been well studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all patients received a single dose of prophylactic antibiotics at induction. It has been debated whether prophylactic antibiotics should be used for percutaneous wiring of fractures and some authors advise against it [14, 15]. Nevertheless, in our cohort, all patients underwent open reduction and subsequent wire fixation, and therefore, the authors felt that prophylactic antibiotics should be used, which is in accordance with our institutional policy.…”
Section: Discussionmentioning
confidence: 66%
“…To minimise SSI occurrences, perioperative prophylactic antibiotics have been routinely used for all patients undergoing ORIF procedures. Although it is generally accepted that prophylactic antibiotics are effective in reducing the incidence of SSI in contaminated and dirty wounds [3,5], it remains uncertain whether antibiotics should be used routinely with patients undergoing clean ORIF surgeries who are at low risk of developing SSI [13,17].…”
Section: Introductionmentioning
confidence: 99%